2014
DOI: 10.1002/micr.22222
|View full text |Cite
|
Sign up to set email alerts
|

Combined medialis pedis and medial plantar fasciocutaneous flaps for coverage of soft tissue defects of multiple adjacent fingers

Abstract: Soft tissue defects of adjacent multiple fingers covered by a single large flap require secondary separation of the flap into each finger. Such covering obstructs independent motion of injured fingers until the single large flap is separated. This report describes the technique of combined medialis pedis and medial plantar fasciocutaneous flaps for reconstructing soft tissue defects of multiple adjacent fingers. Three male patients (age range, 18-33 years) underwent soft tissue reconstructions of multiple adja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…Given the thinness of the soft tissue in this area, it is perhaps the optimal donor site for free flaps, especially when covering small-to medium-sized defects of the hand [18,25,39].…”
Section: Discussionmentioning
confidence: 99%
“…Given the thinness of the soft tissue in this area, it is perhaps the optimal donor site for free flaps, especially when covering small-to medium-sized defects of the hand [18,25,39].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we decided to reconstruct with a flap. There are many other flaps for reconstruction of this case including local/distant flaps and free flaps such as medial plantar flap, medialis pedis flap, and venous flap, that we offered as reconstructive options before the treatment . Because the patient desired a concealable donor site with less morbidity, we decided to use a flap from the lower‐abdominal/inguinal region.…”
Section: Discussionmentioning
confidence: 99%
“…There are many other flaps for reconstruction of this case including local/distant flaps and free flaps such as medial plantar flap, medialis pedis flap, and venous flap, that we offered as reconstructive options before the treatment. [10][11][12] Because the patient desired a concealable donor site with less morbidity, we decided to use a flap from the lower-abdominal/inguinal region. SCIP flap and SIEA flap have a long pedicle suitable for various reconstructions, and their donor scars are well-concealable.…”
Section: Discussionmentioning
confidence: 99%
“…The medialis pedis flap uses a branch of the medial plantar artery as a vascular pedicle and is harvested from the medial side of navicula in the foot. Since its introduction by Masquelet and Romana (1990), the flap has been used to reconstruct defects of the finger pulp (Okada, Saito, Kazuki, & Nakamura, 2014;Rodriguez-Vegas, 2014). Okada et al (2014) reported on 3 cases in which combined medialis pedis and medial plantar fasciocutaneous flaps were elevated to cover soft tissue defects of adjacent fingers.…”
mentioning
confidence: 99%
“…Since its introduction by Masquelet and Romana (1990), the flap has been used to reconstruct defects of the finger pulp (Okada, Saito, Kazuki, & Nakamura, 2014;Rodriguez-Vegas, 2014). Okada et al (2014) reported on 3 cases in which combined medialis pedis and medial plantar fasciocutaneous flaps were elevated to cover soft tissue defects of adjacent fingers. They described the combined flaps as a useful option for the coverage of soft tissue defects involving multiple adjacent fingers.…”
mentioning
confidence: 99%